Enzyme-Loaded pH-Sensitive Photothermal Hydrogels for Mild-temperature-mediated Combinational Cancer Therapy - Xia, Jindong; Qing, Xueqin; Shen, Junjian; Ding, Mengbin; Wang, Yue; Yu, Ningyue; Li, Jingchao; Wang, Xiuhui (Frontiers in Chemistry, 2021)
Photothermal therapy (PTT) that utilizes hyperthermia to ablate cancer cells is a promising approach for cancer therapy, while the generated high temperature may lead to damage of surrounding normal tissues and inflammation. We herein report the construction of glucose oxidase (GOx)-loaded hydrogels with a pH-sensitive photothermal conversion property for combinational cancer therapy at mild‐temperature. The hydrogels (defined as CAG) were formed via coordination of alginate solution containing pH-sensitive charge-transfer nanoparticles (CTNs) as the second near-infrared (NIR-II) photothermal agents and GOx. In the tumor sites, GOx was gradually released from CAG to consume glucose for tumor starvation and aggravate acidity in tumor microenvironment that could turn on the NIR-II photothermal conversion property of CTNs. Meanwhile, the released GOx could suppress the expression of heat shock proteins to enable mild NIR-II PTT under 1064 nm laser irradiation. As such, CAG mediated a combinational action of mild NIR-II PTT and starvation therapy, not only greatly inhibiting the growth of subcutaneously implanted tumors in a breast cancer murine model, but also completely preventing lung metastasis. This study thus provides an enzyme loaded hydrogel platform with a pH-sensitive photothermal effect for mild‐temperature-mediated combinational cancer therapy.